“Enxugando iceberg” como as instituições estatais exercem o controle do crime em São Paulo - Silvestre, Giane (2016)
This research aimed to understand how the institutions and state operators’ crime control are being affected by the emergence of new forms of organization of the "world of crime." It wondered how the institutions and operators find themselves affected by the emergence of the First Command of the Capital, the PCC; which the impact on their work, on the ways to exercise control and institutional management of the crime; which representations they elaborate about the changes in the contexts they operate and develop their professional activities. Therefore, it started analyzing two empirical cases that took place in São Paulo, involving the PCC and the so-‐‑called "debate" -‐‑ a new management mechanism of violence brought from the consolidation of the CPC in and out of the São Paulo prison system. The cases also help to identify two main strategies to crime control in São Paulo: i) a militarized control guided mainly by lethal and selective fighting with alleged criminals, played by the Military Police and; a classic judicial control, in which the logic of the investigation remains linked to archaic model of the police investigation and prioritizes incarceration for certain types of crimes and people, while holding the low levels of punishment for cases of police lethality. Part of the field work was conducted through interviews with civil and military police, sheriffs, prosecutors and judges who work in crime control, including the Special Group Against Organized Crime of the Prosecutor's Office (GAECO). It was developed a research based on official data on crime and on investments in public safety in order to observe trends, preferences and policy choices of area managers in the last decade. The results indicate that the emergence of the PCC has affected the crime control strategies performed by each of these institutions, although continuities have been observed. The PCC started seen as "organized crime", sign often claimed to justify violent and lethal actions in alleged confrontations. Investigations involving the PCC have been recurrently conducted through a partnership between prosecutors and military police, often rather of the judicial police, which has generated tensions between the institutions and their operators. The Civil Police, in its turn, operates with the coexistence of "inquisitorial logic" of investigation and effort to operates the transformations that the emergence of "organized crime" has imposed, besides seeking to circumvent the arising obstacles "scrapping" of institution.